Factors associated with delayed linkage to care following HIV diagnosis in the WHO European Region. (28th February 2018) - Croxford, S; Burns, F; Copas, A; Pharris, A; Rinder Stengaard, A; Delpech, V; ,
Abstract : Objectives: To describe linkage to HIV care following diagnosis in Europe and to identify factors associated with delayed linkage. Methods: We analysed data of adults (aged ≥ 15 years) diagnosed with HIV from 2010 to 2014 in 31 European countries. Linkage to care was calculated using the time between HIV diagnosis and first CD4 count. Linkage was considered delayed if the CD4 count was taken more than 3 months after diagnosis. Logistic regression was used to determine factors for delayed linkage. Results: Of the 120 129 adults diagnosed from 2010 to 2014, 4560 were previously diagnosed elsewhere, 808 died within 3 months of diagnosis and 54 731 people were missing CD4 count and/or date information. Among the 60 030 people included, linkage to care within 3 months was 96%. A lower bound (LB) for this was 55%, when those missing CD4 data were assumed not to be linked. Prompt linkage varied significantly by region [Western: 97% (LB: 65%); Central: 90% (LB: 65%); Eastern: 91% (LB: 11%)] and risk group. In multivariable analysis, delayed linkage to care was associated with: acquiring HIV through injecting drug use/heterosexual contact, being diagnosed in Central/Eastern Europe and having a first CD4 count > 200 cells/μL. People of older age at diagnosis and those diagnosed after 2011 were more likely to be linked promptly. Associations differed by region. Conclusions: Among those with CD4 data available, linkage to care is prompt. However, HIV surveillance must be strengthened and data quality improved, particularly in Eastern Europe. Our findings highlight disparities in care access and significant differences between regions.